Plasma Levels of Vitamin A in Early Pregnancy and Correlationship with Hypertensive Disorder. (18th May 2022) - Lv, Jing; Wang, Yunfeng; Zhao, Yuhua; He, Yingdong; Yang, Huixia; Zhang, Huijing; Wang, Xiaoyu
Abstract : Objective. Analyzing the vitamin A content in early pregnancy and finding out the relationship between the serum levels of vitamin A of pregnant women and hypertensive disorder . Method. A total of 4, 188 pregnant women who had took part in vitamin A testing in Miyun District Hospital from November 2016 to March 2020 were collected. The serum levels of vitamin A were determined by high performance liquid chromatography, and clinical and testing data were collected for statistical analysis. The original data outcome was finally analyzed with the SPSS . Results. 266 Hypertensive disorder cases and 2836 normal pregnancy cases were analyzed with 27 cases of twin pregnancy, 315 cases without follow-up and 744 of diabetic pregnancies excluded. The 266 women were divided into four groups: 110 women were diagnosed gestational hypertension, 65 women were diagnosed preeclampsia, 78 women were diagnosed pregnancy with chronic hypertension, and 13 women were diagnosed chronic hypertension with preeclampsia. The results shows that vitamin A level of the hypertensive group was 0.46(±0.08) mg/L, 0.47 (±0.012) mg/L, 0.47 (±0.09) mg/L, and 0.52 (±0.012) mg/L, respectively, while the level of normal group was 0.44 (±0.09) mg/L. We found that there were differences between the normal pregnant group and the preeclampsia group with statistical significance (P < 0.05 ). The difference between the pregnancy with chronic hypertension group and the normal group was statistically significant (P < 0.05 ). The difference between the chronic hypertension with preeclampsia group and the normal group was also statistically significant (P < 0.05 ) . Conclusion. Serum levels of vitamin A in early pregnant women have a certain correlation with the hypertensive disorder.